Implicit Associations With Nature and Urban Environments: Effects of Lower-Level Processed Image Properties - Menzel, Claudia; Reese, Gerhard (Frontiers in Psychology, 2021)
Nature experiences usually lead to restorative effects, such as positive affective states and reduced stress. Even watching nature compared to urban images, which are known to differ in several image properties that were processed at early stages, can lead to such effects. One potential pathway explaining how the visual input alone evokes restoration is that image properties processed at early stages in the visual system evoke positive associations. To study these automatic bottom-up processes and the role of lower-level visual processing involved in the restoring effects of nature, we conducted two studies. First, we analysed nature and urban stimuli for a comprehensive set of image properties. Second, we investigated implicit associations in a dichotomous set of nature and urban images in three domains, namely valence, mood, and stress restoration. To examine the role of lower-level processing in these associations, we also used stimuli that lacked the spatial information but retained certain image properties of the original photographs (i.e., phase-scrambled images). While original nature images were associated with ‘good’, ‘positive mood’, and ‘restoration’, urban images were associated with ‘bad’ and ‘stress’. The results also showed that image properties differ between our nature and urban images, and that they contribute to the implicit associations with valence, although spatial information and therefore recognition of the environment remained necessary for positive associations. Moreover, lower-level processed image properties seem to play no or only minor roles for associations with mood and stress restoration.